Nietzsche’s “Historical” Jesus: The Crucified Free-Spirit and Bringer of Glad Tidings - Magrini, James (Philosophy and Realistic Reflection, 2025)
Elements of Theology and New Testament scholarship are interwoven into this essay to supplement the reading of Nietzsche’s “historical” Jesus as it appears in The Anti-Christ. The paper unfolds in four sections: First, thoughts are offered regarding Nietzsche’s methodological approach to his reading, and Nietzsche interprets Jesus as representing a unique and “paradigmatic individual.” Second, a detailed examination of Jesus’ ministry and relationship to God and the Holy Kingdom reveals unique elements of Nietzsche’s reading: Jesus as “symbolist,” “free spirit,” and bringer of “glad tidings” (one who dwells in God’s love and presence). Nietzsche’s reading is unique in that he interprets the living Kingdom of God in terms of a “present” manifestation and reality, offering a decidedly “anti-apocalyptic” view of Jesus, who is concerned with opening and inviting others into a reality devoid of the ontological distance separating God and humanity. Third, the essay offers thoughts on why the early Christians and later the established Church “mythologized” Jesus, for when they failed to plumb the depths of his esoteric symbolism, misinterpreted his mission and vocation, they created the fictitious apocalyptic messiah the world now knows, one who supposedly died for the sins of the world. Final thoughts are then offered regarding the impact of Nietzsche’s reading. Jesus is not understood by Nietzsche in terms that are adversarial; instead, he holds Jesus in high regard because of the responsibility demonstrated for his appointed task and spiritual vocation, which ultimately led to his fateful death on the cross.